PENGARUH UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONBILITY DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Erawati, Teguh; Ayem, Sri; Ayudiyati, Prismadini (Pascasarjana Universitas Sultan Ageng Tirtayas, 2018)
This study aims to determine the effect of the size of the company on corporate social responbility disclosure by profitability as a moderating variable. This research was conducted on manufacturing companies in the otomotif sub sector listed on Indonesia Stock Exchange (BEI) period 2012-2016. The population in this study amounted to 13 companies. The sample was chosen by purposive sampling technique, so that the total sample was 9 companies. Data testing method used is linier regression analysis and moderated regression analysis (MRA). The results of this research show that the size of the company has positive effect on corporate social responbility disclosure with a significance level of 0,001. The profitability has significant of moderating but able to weaken the relationship between size of the company to corporate social responbility disclosure with a significance level of 0,010.Keyword : The size of company, profitability, corporate social responbility disclosure